Settlement Services in the Training and Education of Immigrants: Toward a Participatory Mode of Governance. Issue 146 (16th June 2015) - Shan, Hongxia
Abstract : This chapter focuses on the shifting roles that settlement services play in immigrant training and education and advocates a mode of participatory governance.